The impact of educational policies in Southeast Asia - Sharma, C.L (Education quarterly.)
The Southeast Asian countries have reposed implicit faith in the rapid quantitative expansion of educationas the most potent instrument for accelerated national development. The educational policies pursues therefore have not produced the desired results. Therefore, a significant reorientation of the policies would be necessary for institutions both within and without the educational system